2022
DOI: 10.3389/fnagi.2022.977332
|View full text |Cite
|
Sign up to set email alerts
|

High ratio of monocytes to high-density lipoprotein is associated with hemorrhagic transformation in acute ischemic stroke patients on intravenous thrombolysis

Abstract: BackgroundHemorrhagic transformation (HT) is a frequent, serious complication in acute ischemic stroke patients on intravenous thrombolysis. Here we investigated whether risk of HT is associated with the ratio of monocyte count to high-density lipoprotein level (MHR).Materials and methodsMedical records were retrospectively examined for consecutive patients with acute ischemic stroke who received thrombolytic therapy. HT was diagnosed by computed tomography at 24–36 h after therapy. Potential association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Towards the same direction, Xia et al [ 54 ], questioned if patients with AIS receiving IVT would benefit from using the MHR as a predicting factor for HT. Consequently, they conducted a study to investigate whether IVT is associated with MHR and HT and in what manner.…”
Section: Discussionmentioning
confidence: 99%
“…Towards the same direction, Xia et al [ 54 ], questioned if patients with AIS receiving IVT would benefit from using the MHR as a predicting factor for HT. Consequently, they conducted a study to investigate whether IVT is associated with MHR and HT and in what manner.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Recently, a meta‐analysis that involved 9 studies indicated that for patients with coronary heart disease, increased MHR value might be associated with higher long‐term mortality and major adverse cardiovascular events. 26 Nevertheless, some studies have explored the relationship between MHR and short‐term stroke prognosis based on small sample size data from one single center but reported inconsistent results for hemorrhagic transformation 27 , 28 and for all‐cause mortality. 20 , 22 The discrepancy might be due to the differences in the patients' characteristics, and the small sample size with limited statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…A high MHR is an independent predictor of 30-day mortality in ischemic stroke patients, 23 and a cohort study based on rural Chinese populations suggested a higher risk of ischemic stroke in groups with high levels of MHR. 24 Xia et al 25 analyzed 340 patients who underwent IVT and observed that the MHR was higher in patients with HT than in those without HT.…”
Section: Discussionmentioning
confidence: 99%